56.7k views
4 votes
(-6) + 11 + (-4) - (-8)

2 Answers

1 vote

Assignment:
\bold{Solve \ Equation: \ \left(-6\right)+11+\left(-4\right)-\left(-8\right)}

<><><><><><><>

Answer:
\boxed{\bold{9}}

<><><><><><><>

Explanation:
\downarrow\downarrow\downarrow

<><><><><><><>

[ Step One ] Add / Subtract (Left To Right)


\bold{\left(-6\right)+11=5}

[ Step Two ] Rewrite Equation


\bold{5+\left(-4\right)-\left(-8\right)}

[ Step Three ] Apply Rule
\bold{+\left(-a\right)\:=\:-a: \ +\left(-4\right)=-4}


\bold{5-4-\left(-8\right)}

[ Step Four ] Subtract: 5 - 4 = 1


\bold{1-\left(-8\right)}

[ Step Five ] Apply Rule
\bold{-\left(-a\right)\:=\:+a: \ -\left(-8\right)=+8}


\bold{1+8}

[ Step Six ] Solve


\bold{=9}

<><><><><><><>


\bold{\rightarrow Mordancy \leftarrow}

User Sergey Ratnikov
by
4.9k points
3 votes

Answer: 9

Explanation:

To solve this problem you must apply the proccedure shown below:

Keeping on mind that:

(-)(-)=+

(+)(+)=+

(-)(+)=-

You can distribute the signs as following:


-6+11-4+8

Now, you can add all the numbers shown above. Therefore, you obtain the following sum:


=9

User Matt Hancock
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.